2016
DOI: 10.22514/sv121.102016.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of population-based training programs on bystander willingness to perform cardiopulmonary resuscitation

Abstract: Objective. This study was performed to determine the factors related to unwillingness of bystanders to perform cardiopulmonary resuscitation (CPR), and improvement of willingness among the lay public after CPR training. Design. Retrospective designMethods. We collected questionnaires received from laypersons attending CPR training courses implemented by the CPR Improvement Program of Chang Gung Memorial Foundation. Pre-and posttraining questionnaires were given to participants attending CPR training courses be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…This is in keeping with the findings of a study that was conducted in China where the majority (98.6%) of participants interviewed were willing to perform CPR on a family member compared to a stranger (76.3%) [21]. However, another Chinese study showed that CPR training was associated with a significant increase in willingness to perform CPR on a stranger [22].…”
Section: Discussionsupporting
confidence: 87%
“…This is in keeping with the findings of a study that was conducted in China where the majority (98.6%) of participants interviewed were willing to perform CPR on a family member compared to a stranger (76.3%) [21]. However, another Chinese study showed that CPR training was associated with a significant increase in willingness to perform CPR on a stranger [22].…”
Section: Discussionsupporting
confidence: 87%
“…For this study, participants were enrolled in the Love GOGO program from January to December 2017. Based on our previous study, both traditional and blended teaching models showed a noticeable decline in skill retention after approximately 6 months [ 12 , 15 ]. In this study, mandatory retraining was administered every 6 months or 1 year ( Figure 1 ), spanning a comprehensive training regimen conducted over 2 years.…”
Section: Methodsmentioning
confidence: 99%
“…After initial training but before refresher training, we collected data regarding BLS knowledge, skill tests, and CPR quality at the scene at 12 and 24 months. The BLS knowledge and skill tests received approval from the Chairman of the Taiwan Society of Emergency Medicine and have also been published in previous studies [ 12 , 15 ] ( Multimedia Appendices 1 and 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations